PEMETAAN TANAH WAKAF DI KABUPATEN KARAWANG - Fakhruddin Fakhruddin (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2018)
Abstract This research describes the implementation of wakaf land certification policy in Kota Karawang, West Java Province. This study uses a qualitative approach and explains the fact that, the data on the status of uncertified wakaf land is still much larger than that already certified, most of the land use / use of waqf land is mostly used for mosques and mushalla, administrative and coordinative processes and performance which need to be improved to minimize the occurrence of data discrepancies. Four things become an indicator and then concluded that the understanding of society is done solely for places of worship that its use is intended as a mosque, mushola, and educational institutions and other purposes that benefit the interests of the ummah. Awareness of community representation emerged and maintained due to the strong role of religious leaders. In relation to land wakaf land mapping data in Karawang, there are differences in the amount of wakaf land data published by three institutions, should not occur if there is a work synchronization and maximum coordination between the three institutions. There is a dispute on wakaf land in Karawang caused by the lack of public awareness about the importance of administration perwakafan. Office of the Ministry of Religious Affairs Karawang regency needs to cooperate more intensively dengen Government Karawang and BPN in acceleration of land certification through coaching and socialization perwakafan. The lack of budget for perwakafan posts in the Ministry of Religious Affairs Karawang regency has contributed to the weakness of the process of certification of wakaf land.